UJI PENDAHULUAN DAN KARAKTERISASI SIMPLISIA HERBA PICISAN (Drymoglossum piloselloides (L.) presl) - Lia Fikayuniar; Julia Ratnawati; Yenny Febriani Yun (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2016)
abstrak